PENILAIAN TINGKAT KAPABILITAS TATA KELOLA TEKNOLOGI INFORMASI PADA ASPEK MANAJEMEN SUMBER DAYA MANUSIA (STUDI KASUS BPK RI) - , Rahmi Novita, Dr. Ir. Eko Nugroho, M. Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
IT governance is one of the main drivers of business transform ation process towards good governance. To support the management of IT governance, IT human resources needs competent. This study to assess the level of IT governance capability in aspects of Human Resources management. The instruments used in this study is COBIT 5. The four stages are carried out in this study is the first stage of the initial literature review, document review and formulation of the background and benefits of the research objectives . The second is the stage of problem solving involves the identification of IT-related goals , mapping IT-related goals with COBIT 5 process, the preparation of the questionnaire and the determination of the respondent. The third stage of the formulation of the problem, analysis of data and the fourth stage or finally stage deduced. Assessing the Capability level refers to the process of COBIT Process Assessment Standard Model (PAM) from ISACA . The results of the assessment of IT governance capability in the management aspects of the 13 whom have valuation process known two processes are at level 0, the eight processes at level 1, one process at level 2 and two at level 3 processes .